Early Detection of Sepsis With Machine Learning Techniques: A Brief Clinical Perspective - Giacobbe, Daniele Roberto; Signori, Alessio; Del Puente, Filippo; Mora, Sara; Carmisciano, Luca; Briano, Federica; Vena, Antonio; Ball, Lorenzo; Robba, Chiara; Pelosi, Paolo; Giacomini, Mauro; Bassetti, Matteo (Frontiers in Medicine, 2021)
Sepsis is a major cause of death worldwide. Over the past years, prediction of clinically relevant events through machine learning models has gained particular attention. In the present perspective, we provide a brief, clinician-oriented vision on the following relevant aspects concerning the use of machine learning predictive models for the early detection of sepsis in the daily practice: (i) the controversy of sepsis definition and its influence on the development of prediction models; (ii) the choice and availability of input features; (iii) the measure of the model performance, the output, and their usefulness in the clinical practice. The increasing involvement of artificial intelligence and machine learning in health care cannot be disregarded, despite important pitfalls that should be always carefully taken into consideration. In the long run, a rigorous multidisciplinary approach to enrich our understanding in the application of machine learning techniques for the early recognition of sepsis may show potential to augment medical decision-making when facing this heterogeneous and complex syndrome.